Mallet Finger Fracture through Enchondroma of the Distal Phalanx - Wakasugi, Takuma; Suzuki, Hidetsugu; Shirasaka, Ritsuro (Journal of Hand and Microsurgery, 2019)
A 46-year-old man injured his ring finger and developed a mallet deformity. Radiographs showed a mallet finger fracture through an osteolytic lesion of the distal phalanx. Magnetic resonance imaging showed low intensity on T1-weighted imaging and high intensity on T2-weighted imaging, which suggested the clinical diagnosis of enchondroma. The bone tumor was excised, and osteosynthesis was performed using Ishiguro's extension block pinning, and a flexion block pin was added to prevent flexor tendon avulsion fracture through the enchondroma, followed by an autologous iliac cancellous bone graft. One year after surgery, the patient had no pain or extension lag of the affected ring finger, and his quickDASH score was 0 points. Radiographs showed no recurrence and minimal arthritic change of the distal interphalangeal joint. One-stage treatment of a mallet finger fracture through an enchondroma using Ishiguro's method was effective.
Keywords: mallet finger; enchondroma; pathologic fracture; osteosynthesis